Perioperative trajectory of plasma viscosity: A prospective, observational, exploratory study in cardiac surgery. (21st July 2022) - Valeanu, Liana; Andrei, Stefan; Ginghina, Carmen; Robu, Cornel; Ciurciun, Adrian; Balan, Cosmin; Stefan, Mihai; Stoian, Anca; Stanculea, Iulia; Cheta, Andreea; Dima, Laura; Stiru, Ovidiu; et al.
Abstract: Objective: Plasma viscosity is one of the critical factors that regulate microcirculatory flow but has received scant research attention. The main objective of this study was to evaluate plasma viscosity in cardiac surgery with respect to perioperative trajectory, main determinants, and impact on outcome. Methods: Prospective, single center, observational study, including 50 adult patients undergoing cardiac surgery with cardiopulmonary bypass between February 1, 2020 and May 31, 2021. Clinical perioperative characteristics, short term outcome, standard blood analysis, plasma viscosity, total proteins, and fibrinogen concentrations were recorded at 10 distinct time points during the first perioperative week. Results: The longitudinal analysis showed that plasma viscosity is strongly influenced by proteins and measurement time points. Plasma viscosity showed a coefficient of variation of 11.3 ± 1.08 for EDTA and 12.1 ± 2.1 for citrate, similarly to total proteins and hemoglobin, but significantly lower than fibrinogen ( p < .001). Plasma viscosity had lower percentage changes compared to hemoglobin (RANOVA, p < .001), fibrinogen (RANOVA, p < .001), and total proteins (RANOVA, p < .001). The main determinant of plasma viscosity was protein concentrations. No association with outcome was found, but the study may have been underpowered to detect it. Conclusion: Plasma viscosity had a low coefficient of variation and low perioperative changes, suggesting tight regulation. Studies linking plasma viscosity with outcome would require large patient cohorts.